Characterization of Gene Expression Suppression by Bovine Coronavirus Non-Structural Protein 1 - Ohkami, Takehiro; Kitashin, Ichika; Kawashima, Riko; Yoshida, Aimi; Saito, Taizo; Takashima, Yasuhiro; Kamitani, Wataru; Nakagawa, Keisuke (Viruses, 2025)
Coronavirus non-structural protein 1 (nsp1) is a pathogenic determinant of Betacoronaviruses. Previous studies demonstrated that the nsp1 of various coronaviruses induces host shutoff through a variety of mechanisms; however, there is little information on the function of bovine coronavirus (BCoV) nsp1. We aimed to characterize the host gene expression suppression function of BCoV nsp1. We first confirmed that the expression of BCoV nsp1 in MAC-T cells, a bovine mammary epithelial cell line, suppressed host and reporter gene expression. Subsequently, lysine and phenylalanine at amino acid positions 232 and 233, respectively, were identified as key residues required for this suppressive effect. Expression levels of housekeeping genes are comparable in cells expressing wild-type BCoV nsp1 and a mutant with alanine substitutions at positions 232 and 233 (BCoV nsp1-KF). Wild-type BCoV nsp1 localized to both the cytoplasm and nucleus; however, BCoV nsp1-KF exhibited prominent nuclear accumulation with dot-like structures. Using confocal microscopy and co-sedimentation analysis, we identified an association between wild-type BCoV nsp1, but not BCoV nsp1-KF, and ribosomes, suggesting that ribosome binding is required for BCoV nsp1-mediated suppression of host gene expression. This is the first study of the characterization of host gene expression suppression by BCoV nsp1.